Toward a primate model of l-dopa-unresponsive parkinsonism mimicking striatonigral degeneration - Ghorayeb, Imad; Fernagut, Pierre O.; Aubert, Incarnation; Bezard, Erwan; Poewe, Werner; Wenning, Gregor K.; Tison, François (Movement disorders, 2000)
We developed a primate model of striatonigral degeneration (SND), the neuropathology underlying levodopa‐unresponsive parkinsonism associated with multiple systemic atrophy (MSA‐P), by sequential systemic administration of 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (MPTP) and 3‐nitropropionic acid (3NP) in a Macaca fascicularis monkey. l‐Dopa‐responsive parkinsonian features emerged after MPTP injections. Subsequent chronic 3NP administration aggravated the motor symptoms and abolished the l‐dopa response. In vivo magnetic resonance imaging revealed bilateral striatal lesions. Histopathologically, there was severe dopaminergic cell loss in the substantia nigra pars compacta compared with the control monkey. Furthermore, we observed circumscribed areas of severe neuronal degeneration in the motor striatum. These changes were absent in the control monkey, and they were associated with diffuse metabolic failure as demonstrated by cytochrome oxidase histochemistry. The striatal pathology predominantly involved output pre‐pro‐enkephalin A‐ and substance P‐containing cells, whereas somatostatin (NADPH‐diaphorase)‐containing interneurons were relatively spared. Our model therefore reproduced levodopa‐unresponsive parkinsonism and SND‐like pathologic changes characteristic of MSA‐P. The double‐lesion primate model of SND may serve as a preclinical test‐bed for the evaluation of novel therapeutic strategies in MSA‐P.